2005
DOI: 10.1007/s10753-006-8967-1
|View full text |Cite
|
Sign up to set email alerts
|

IL-18 Receptor Expression on Epithelial Cells is Upregulated by TNF Alpha

Abstract: IL-18 is a multifunctional cytokine that augments both innate and acquired immunity and potentiates Th1 and Th2 reactions. We studied the expression of IL-18 receptor (IL-18R) on renal and respiratory epithelial cell lines. Both cell lines upregulated IL-18R mRNA and IL-18R membrane expression in response to TNF alpha and other proinflammatory cytokines. The function of IL-18R was confirmed by induction of IL-8 release from epithelial cells in response to recombinant IL-18. Epithelial cells may represent an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…IL-18Rα expression has been demonstrated in renal tubular epithelial cells in vitro, and shown to be upregulated in response to stimulation with TNF-α and other proinflammatory cytokines [12]. Our study has shown that while appreciable levels of IL-18Rα are expressed in glomeruli, IL-18Rα mRNA and protein are undetectable in untreated and stimulated wild-type primary MCs.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…IL-18Rα expression has been demonstrated in renal tubular epithelial cells in vitro, and shown to be upregulated in response to stimulation with TNF-α and other proinflammatory cytokines [12]. Our study has shown that while appreciable levels of IL-18Rα are expressed in glomeruli, IL-18Rα mRNA and protein are undetectable in untreated and stimulated wild-type primary MCs.…”
Section: Discussionmentioning
confidence: 47%
“…IL-18 is also known to induce the production of IL-2, granulocyte-macrophage colony-stimulating factor and IL-2 receptor (α-chain). IL-18 is involved in the pathophysiology of autoimmune disorders such as LN, as well as crescentic glomerulonephritis, diabetic nephropathy and allograft rejection [12,13,14,15,16]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, an explanation could be that low levels of IL-18 may be due to the presence of IL-18R in gingival epithelia. It has been reported that the expression of IL-18R on renal and epithelial cell lines can be induced in response to TNF alpha and other proinflammatory cytokines [30]. Another important aspect which may explain the low levels of IL-18 in diabetic patients with PD, is the neutrophils' function in the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…This cytokine binds to its receptor IL‐18R1 and activates inflammatory signalling pathway (Azam et al, ). The pro‐inflammatory cytokines such as TNF and IL‐1 upregulate IL‐18R1 expression in epithelial cells and enhance IL‐8 secretion (Krásná et al, ).…”
Section: Introductionmentioning
confidence: 99%